A Lei Modelo Interamericana para prevenir, punir e erradicar a morte violenta de mulheres (femicídio/feminicídio) e a difusão de normas de combate à violência de gênero na América Latina - Oliveira, Cristiane Rocha (2022)
This paper aims to analyze how the process of dissemination of norms related to gender violence in Latin America took place and to relate this process to the Inter-American Model Law to Prevent, Punish and Eradicate the Violent Death of Women, published in 2018 within the scope of the Organization of the American States (OAS). For this purpose, the research was based on primary sources, such as documents produced by the Inter-American Commission of Women and by the Follow-up Mechanism of the Convention of Belém do Pará, within the scope of the OAS; and secondary sources, composed of selected literature on the elaboration of anti-violence regulations at regional levels and on the theory of norm diffusion (FINNEMORE; SIKKINK, 1998; ROGGEBAND, 2016; SILVA, no prelo; ARAI, 2020; COPELLO, 2012). This article provided the analysis of the unique process of diffusion of norms to combat femicide in Latin America, which resulted in the materialization of the Model Law, that is, it sought to understand what differentiated this Model Law from other existing ones, since there was a bottom up diffusion process of this law even with its elaboration following the top down model